Economic evaluation of cognitive behavioral therapy and Internet-based guided self-help for binge-eating disorder - König, Hans-Helmut; Friederich, Hans-Christoph (The international journal of eating disorders, 2018)
To determine the cost-effectiveness of individual face-to-face cognitive behavioral therapy (CBT) compared to therapist guided Internet-based self-help (GSH-I) in overweight or obese adults with binge-eating disorder (BED).